Light curing resin cements containing iodonium salts promote suitable apical bonding of posts to radicular dentin - Thatiana de Vicente LEITE; Andrea Nóbrega CAVALCANTI; Adriano Fonseca de LIMA; Luciano de Souza GONÇALVES; David Christopher WATTS; Giselle Maria Marchi BARON; Luis Roberto Marcondes MARTINS (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract The aim of this study was to analyze the efficiency of experimental light-curing resin cements (ERCs) with a ternary photo-initiator system containing diphenyliodonium hexafluorphosphate (DPI) and different amines on retention of glass-fiber posts to dentin (GFP). ERCs formulations: a 1:1 mass ratio of 2,2-bis[4-(2-hydroxy-3-methacryloxypropoxy)phenylpropane and triethyleneglycol dimethacrylate. Camphorquinone was used as initiator. Six experimental groups were established according to the amine used: [ethyl-4-(dimethylamino)benzoate-EDMAB or 2-(dimethylamino)ethyl methacrylate-DMAEMA] and the concentration of DPI (0, 0.5 mol%, 1 mol%). The resin cements Variolink II (dual- and light-cured versions) were used as commercial reference. Eighty recently extracted bovine incisors (n = 10) were selected for this study. The roots were prepared and the fiber posts were cemented with the resin cement specified for each experimental group. Specimens from coronal, middle, and apical thirds of the root were subjected to push-out bond strength test 24 hours after bonding. Data were subjected to split-plot ANOVA and the Tukey test (p = 0.05). ERCs containing DPI showed statistically significant higher bond strengths compared with ERCs without DPI. ERCs containing DPI were statistically similar to VARIOLINK II - dual-cured and superior to VARIOLINK II - light-cured (except for EDMAB - 1DPI in the medium third and DMAEMA - 1DPI in the coronal third). Different amines did not influence post retention. The apical root region showed the lowest bond strength for the groups EDAB-0DPI, DMAEMA-0DPI and VARIOLINK II light-cured. Light-cured ERCs containing DPI were efficient for GFP retention to radicular dentin, with similar behaviour to that of dual-curing commercial resin cement.